Pendampingan Intensif Pembuatan Konten dan Media Komunikasi Digital untuk Meningkatkan Layanan Puskesmas melalui Teknologi dan Strategi Digital - Soegiarto, Asep; Kholik, Abdul; Rosalina, Indah Fajar; Qoryna Noer Seyma El Farabi (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
This community service program aims to improve the quality of services at Puskesmas (community health centers) through intensive assistance in content creation and digital communication media. The main issue addressed is the low digital literacy among healthcare workers at Puskesmas in managing effective communication media to reach the public. This has led to low community participation in health programs run by Puskesmas. Therefore, this program is designed to enhance healthcare workers' skills in utilizing digital technology for health promotion and improving communication effectiveness with the public. The program implementation involves several stages: (1) an initial survey to assess the condition of existing communication media, (2) training on creating engaging and informative health education content, (3) workshops on graphic design and health promotion video creation, (4) guidance on using social media platforms to disseminate health information, and (5) continuous evaluation and monitoring to ensure the sustainability of the program. This activity involves 25 healthcare workers from 5 selected Puskesmas, with a mentoring duration of 6 months. The results show significant improvements, including: an increase in healthcare workers' ability to create digital content from 30% to 85%, a 200% increase in public engagement with health information, and a 150% increase in the coverage of health promotion services. Additionally, the program has produced 120 pieces of health education content, 15 health promotion videos, and 8 successful digital campaigns that have successfully enhanced public participation in health programs. The long-term impact of this program is the increased public awareness of preventive health and improved access to Puskesmas services. This program can also be replicated in other regions as a model for improving the quality of primary healthcare services through optimal use of digital technology, which can accelerate the achievement of national health development goals.